THE INFLUENCE OF CORE SELF EVALUATIONS ON THE WORK MOTIVATION OF PUBLIC RELATIONS PRACTITIONERS IN HOTEL BUSINESS COMPETITION IN THE GLOBALIZATION ERA - Nisrin Husna (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2019)
Abstractâ€” In this globalization era, hospitality or hotelier investment opportunities are growing rapidly, but not without a formidable competition, which is why these growing opportunities and threats have to be recognised by the people in this industry. One of the most important strategy in facing the global era business competition is to convince the costumerÂ  that the hotel they are chosing is better and has more benefits than the rest of the competition. Convincing the customer means building a relation through positive perception, positive image and positive experiences to finally gain their trusts. This is where a highly motivated Public Relations is needed as the frontline of the company. Judge, Erez & Bono (1998) stated that self esteem, self efficacy and the locust of control are the three core-self evaluation that form the basic for building individual work motivation.The purpose of this study is to see the influences of these three core-self evaluation on the work motivation of Public Relations in facing the hotel business competition. When analyzing the influences of these three variables on the work motivation of a Public Relations, the researcher uses the cybernetic tradition approach. Through this approach the researcher then uses the Expectancy Value Theory in analyzing the influences of self esteem, self efficacy, and the locus of control on the work motivation.The sample of this research is the Public Relations practitioner of Santika Indonesia Hotel and Resort. This research uses the path analysis technique. The SPSS calculation shows that the three variables bring positive influences towards the work motivation with the self efficacy line coefficient value of 0.322, self efficacy 0.340, and the locus of control with 0.346.These results show that the more positive the self esteem, self efficacy and the locus of control value of a Public Relations, the higher the work motivation of the Public Relations of Santika Hotel and Resort in facing the business competition in this global era.